Accommodation and stereopsis in adults with traumatic brain injury. (12th March 2020) - Chen, Na; Liao, Meng; Yang, Chaohua; Liu, Longqian
Abstract : Background: Traumatic brain injury has many adverse effects on visual functions. The aim of this study is to evaluate accommodation, stereopsis deficits and visual symptoms in Chinese patients with traumatic brain injury. Methods: This is a cross‐sectional study that included 22 patients with traumatic brain injury and 22 controls; the refractive status, stereoacuity, and accommodative ability of each subject were measured. Results: Patients with traumatic brain injury were significantly more symptomatic than controls (p < 0.001). Near stereoacuity thresholds were significantly elevated in patients with traumatic brain injury compared to controls (p < 0.001). Accommodative amplitude (right eye: p = 0.007; left eye: p = 0.01; both eyes: p = 0.002) and accommodative facility rates (right eye: p < 0.001; left eye: p < 0.001; both eyes: p < 0.001) were significantly lower in patients with traumatic brain injury, for whom there were no significant differences between the accommodative facility rates of the pre‐ and post‐three‐minute binocular flipper sessions (p = 0.51). Patients with traumatic brain injury showed greater accommodative lag to 2.5 D (p = 0.03), 3 D (p = 0.03), 4 D (p = 0.004) and 5 D (p = 0.001) stimuli, but not to the 2 D (p = 0.10) stimulus. The regression equation of accommodative lag to stimuli was steeper for the traumatic brain injury group (slope: p = 0.01; y‐intercept: p < 0.0001). There were also significant correlations between visual symptoms and clinical findings including binocular accommodative amplitude (r = −0.480, p = 0.001), binocular accommodative facility (r = −0.445, p = 0.004) and stereopsis (r = 0.457, p = 0.002). Conclusion: Patients with traumatic brain injury have deficits in accommodation and stereopsis.